2014
DOI: 10.1016/j.sdj.2014.10.001
|View full text |Cite
|
Sign up to set email alerts
|

An ageing population poses dental challenges

Abstract: In this narrative review paper, we summarise what is known about the oral health of older people, with a specific focus on the most common oral conditions in that age group. After that, the implications for older people׳s oral care are considered, along with ways of developing and maintaining a gerodontologically capable and responsive workforce and oral care delivery system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
54
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(55 citation statements)
references
References 55 publications
1
54
0
Order By: Relevance
“…The study showed that the age group of 75+ years in 2015 increased their need for oral surgery and restorative treatment (Table b). Table portrays the pattern of ongoing dental demand and access patterns that reflects Thomson and Ma (2014) observations of continuing inequities due to behavioural patterns in the everyday life of the elderly …”
Section: Discussionmentioning
confidence: 96%
“…The study showed that the age group of 75+ years in 2015 increased their need for oral surgery and restorative treatment (Table b). Table portrays the pattern of ongoing dental demand and access patterns that reflects Thomson and Ma (2014) observations of continuing inequities due to behavioural patterns in the everyday life of the elderly …”
Section: Discussionmentioning
confidence: 96%
“…Because of new treatment modalities and preventative measures, a downward trend in edentulism prevalence has been widely reported in recent years, especially in many developed countries. However, the trend of tooth loss remains unpredictable in China.…”
Section: Discussionmentioning
confidence: 99%
“…Although the prevalence of edentulism has been projected to decline globally, tooth loss still poses a great challenge to many less developed countries. Because of China's increasing life expectancy and decreasing fertility rate, its elderly population has been rapidly increasing at an average annual rate of 3.32% since 1990.…”
Section: Introductionmentioning
confidence: 99%
“…Prevalence of oral disease similarly increases with age . As people live longer while retaining their natural teeth, the challenges and complexity of their oral health needs grow . Poor oral health can have significant effects on older adults.…”
Section: Introductionmentioning
confidence: 99%